FACTORS INFLUENCING THE DEVELOPMENT OF EARLY CHILDHOOD EDUCATIONAL INSTITUTIONS (PAUD) IN BULO-BULO VILLAGE, PUJANANTING DISTRICT, BARRU DISTRICT: A REVIEW OF THE IMPORTANCE OF THE CONTEXT OF EARLY CHILDHOOD EDUCATION - Jumria; Rais , Rahmi (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal